2020
DOI: 10.3390/mi11020126
|View full text |Cite
|
Sign up to set email alerts
|

Desktop Fabrication of Lab-On-Chip Devices on Flexible Substrates: A Brief Review

Abstract: Flexible microfluidic devices are currently in demand because they can be mass-produced in resource-limited settings using simple and inexpensive fabrication tools. Finding new ways to fabricate microfluidic platforms on flexible substrates has been a hot area. Integration of customized detection tools for different lab-on-chip applications has made this area challenging. Significant advancements have occurred in the area over the last decade; therefore, there is a need to review such interesting fabrication t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Polymer micromolds are fabricated through CNC milling [30], laser ablation [31], or 3D printing [32,33]; these are straightforward methods with low-cost desktop fabrication facilities. Such facilities also require fewer operating skills, enabling broad usage [3,34]. However, surface defects, such as milling marks and those due to overheating, or poor printing resolution resulting from the use of related techniques may result in rough microchannels or micromolds or uneven substrate surfaces, limiting microfluidic device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer micromolds are fabricated through CNC milling [30], laser ablation [31], or 3D printing [32,33]; these are straightforward methods with low-cost desktop fabrication facilities. Such facilities also require fewer operating skills, enabling broad usage [3,34]. However, surface defects, such as milling marks and those due to overheating, or poor printing resolution resulting from the use of related techniques may result in rough microchannels or micromolds or uneven substrate surfaces, limiting microfluidic device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Glass and Silicon were the first substrates used and channels could either be etched or created using photolithography. However, since both these materials are expensive, plastic and polymers are now being used as alternatives (McDonald et al, 2000 ; Qamar and Shamsi, 2020 ).…”
Section: Commonly Used Fabrication Techniques For Poct Devicesmentioning
confidence: 99%
“…86 These platforms can be easily fabricated through desktop wax and inkjet printers. [87][88][89] Specically, it was demonstrated that physisorbed DNA improves the electrochemical property of MoS 2 electrodes, because it reduces the bandgap of the MoS 2 . The electrocatalytic current is sequencedependent, and the hybridization event further enhances the response in the high ionic strength environment, which was translated into ultra-sensitive detection of CGG trinucleotide repeats associated with fragile X-associated tremor/ataxia syndrome.…”
Section: D Interfacementioning
confidence: 99%